2016
DOI: 10.1038/srep36091
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity and Anthropometric Indicators as Screening Tools of Metabolic Syndrome among Low Income Rural Adults in Xinjiang

Abstract: Most previous studies on metabolic syndrome (MetS) examined urban and high income settings. We thus investigated the prevalence of MetS among a multi-ethnic population living in a low income rural area and explored the use of visceral adiposity and anthropometric indicators to identify men and women with MetS. We recruited 10,029 individuals of nomadic Kazakhs, rural Uyghur and Han residents in Xinjiang, China. MetS was defined by the Joint Interim Statement criteria. The receiver operating characteristic curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 43 publications
4
44
1
2
Order By: Relevance
“…This value shows good capacity to identify adult quilombolas who will truly have MetS and consequently a low probability of false-negative results in provisional diagnostic tests replacing the gold standard. These values are similar to 16 or better 12,13,17 than those found in the literature.…”
Section: -Specificitysupporting
confidence: 89%
See 2 more Smart Citations
“…This value shows good capacity to identify adult quilombolas who will truly have MetS and consequently a low probability of false-negative results in provisional diagnostic tests replacing the gold standard. These values are similar to 16 or better 12,13,17 than those found in the literature.…”
Section: -Specificitysupporting
confidence: 89%
“…different adult populations have also shown the MetS screening capacity of BF% 16 , BAI [13][14][15] and BMI 12,[14][15][16][17] . However, to our knowledge, this is the first study to evaluate the capacity of the three main general OIs to screen for MetS in the same study of adults.…”
Section: -Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…The components of the lipid panel and other anthropometric parameters were used to calculate the central obesity indices, such as the visceral adiposity index and lipid accumulation product. The VAI for males = [WC/(39.68+(1.88 x BMI)] x [TG (mg/dl) /1.03] x [1.31/HDL (mg/dl) ], and the VAI for females = [WC/(36.58+(1.89 x BMI)] x [TG (mg/dl) /0.81] x [1.52/HDL (mg/dl) ] 15. The LAP was calculated as [{WC(cm) − 65} × {TG (mmol) }] for men and [{WC (cm) − 58} × {TG (mmol) }] for women 16…”
Section: Methodsmentioning
confidence: 99%
“…Kazakhs in Xinjiang, China are nomadic minorities living primarily in remote mountainous areas. The majority fall into a low economic class and their culture and customs are signi cantly different from those of other ethnic groups [11,12]. A previous study by our research group found the prevalence of MS in Kazakhs to be higher than that in other ethnic groups in Xinjiang and higher than the national average [13].…”
Section: Introductionmentioning
confidence: 82%